Why Did Józef Czapski Change His View of the Skamandrites? - Mitzner, Piotr (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article applies to Józef Czapski’s – a Polish painter and essayist – personal literary choices; ones that often were contrary to the tastes of his generation. In 1942, after leaving the Soviet bloc, Czapski developed the anthology Polskie wiersze wojenne for Russian readers, and the events of the war caused him to change his opinion about the modern poetry. Poems by the Skamandrites, whom he had disregarded for a long time, now became the core of his collection. Having been found a few years back, the anthology was published in 2019.